RESISTIVITY ANOMALY AT MOUNT KABA, BENGKULU, INDONESIA, AS INFERRED FROM GEOELECTRICAL INVESTIGATION - Titi Anggono; Syuhada Syuhada; Bogie Soedjatmiko (Widyariset, 2013)
Mount Kaba is a volcano located in the magmatic arc Bukit Barisan near the town of Curup, Rejang Lebong, Bengkulu, Indonesia. Two geothermal manifestations have been found in this region in form of hot springs at Suban Airpanas (50oC) and Sindangjati (37oC). Geoelectrical survey based on Schlumberger array up to AB/2 2,000 m was carried out in 2009–2011 in the surrounding area of Mt. Kaba. The aim of the investigation was to locate the distribution of low resistivity anomaly layer that may associate with hydrothermally altered subsurface rock in the area. It is estimated that the depth of low resistivity (< 5 ohm-m) found in the eastern part of Mt. Kaba is about 400 m.